(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2024)
The research to focuses on spraying the plant leaves from the bottom and top by developing a sprayer. The sprayer was making a sprayer made of aluminum with a movable arm containing a nozzle holder divided into three pieces. Each piece contains a nozzle of the type Flat Fan 120-C3. The tasting of the sprayer was done in one of the greenhouses of the Department of Horticulture and Forestry. The study has two factors, the first is changing eff changing the positions of the nozzle holder tube to two levels A1, A2. The second factors were the spray pressure with three levels P1=2, P2=3, P3=4 bar. The spraying speed was 3.12 km/h. The effect of the previous factors on the following characteristics namely: spray losses, spray penetration, and spraying homogeneity. The research began in 2021.The experimental design was Randomized Complete Block Design (RCBD) according to the SPLIT-PLOT system and with three replications using a significant difference LSD with a probability level of 0.05. The results showed that the study factors at the level of A1 position and pressure 4 bar were superior to the losses and penetration. The level of A2 and P3 pressure achieved the highest result with the uniformity of the spray.